Ativação de carvão em reator de leito fluidizado - Campos, Plínio Ribeiro Fajardo (1996)
Active carbon is a very important industrial material due to its characteristics of adsorption, presenting several applications. Taking that into account the activation of batches of 80 g of the coconut shell carbon with steam water in a fluidized bed reactor was studied. The reactor was operated in an opened mode with the flue gases coming through a screen perforated at its top. To carry out the present work, it was built an equipment in scale of row seats composed both of a steam water preheater with e1tric resistances and a 310 stainless steel fluidized bed with a 3.7 cm intemal diameter and 74 cm high. The part above the perforated distributor plate, in which the particle fluidization occurs is 37cm high. In this reactor, the heating is completed with an electric resistance, which promotes the activation of carbonized carbon. The activation temperatures were 800 and 900°C and the residence time was 15 to 90 minutes. Mass flow of steam was measured through calibrated orifice. The coconut shell previously carbonized was provided by BRASILAC Chemical Industries Ltd. and after granulometric characterization it resulted in particles of 2.21 mm average diameter, which are appropriate for discontinuous production of granular activated carbon. The main characteristics of the activated carbons produced in the fluidized bed reactor were compared with the ones obtained industrially in slip bed at BRASILAC. Among the industrial parameters for the quality of activated carbon, the iodine index adsorption is used the most and so is the surface area determined by nitrogen adsorption in BET. These parameters showed that the activated carbons produced in fluidized bed present a better quality concerning these indices.